2008
DOI: 10.1002/ange.200800233
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Synthesis of a Pochonin Library Targeting HSP90 and In Vivo Efficacy of an Identified Inhibitor

Abstract: The heat-shock protein 90 (HSP90) has emerged as one of the most exciting therapeutic targets in recent years. [1,2] Despite the seemingly ubiquitous function of this constitutively expressed chaperone, its role in stabilizing conformationally labile proteins has implications in pathologies ranging from oncology to neurodegenerative diseases. Most endogenous clients [3] of HSP90s are key regulators of cell signaling which are destabilized and degraded in the absence of the chaperoning activity of HSP90. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Preliminary experiments with the aryl moiety (fragment A) had shown that modifications of either phenol was detrimental; however, the presence or absence of a chlorine at R 1 did have a subtle impact on the activity and both alternatives were included in the library. We [27] and others [30] had previously found that in the lower part of the macrocycle (derived from fragment B) the saturated fragment B2 was tolerated. However, additional substitutions had not been investigated and three new combinations (B3-5) were included.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Preliminary experiments with the aryl moiety (fragment A) had shown that modifications of either phenol was detrimental; however, the presence or absence of a chlorine at R 1 did have a subtle impact on the activity and both alternatives were included in the library. We [27] and others [30] had previously found that in the lower part of the macrocycle (derived from fragment B) the saturated fragment B2 was tolerated. However, additional substitutions had not been investigated and three new combinations (B3-5) were included.…”
Section: Resultsmentioning
confidence: 96%
“…The last group (D) included the largest diversity to probe the optimal oxime substituent. [27,31,32] As shown in Scheme 2, deprotonation of the toluate fragment A with LDA followed by the addition of fragment B afforded a total of ten different combinations of intermediate 2 www.chembiochem.org in moderate to good yield (50-85 %), except for the coupling with fragment B2, which was afforded unacceptable yield (< 10 %); this is presumably due to competing enolization of the Weinreb amide. Alternatively, the same product could be obtained by conjugate reduction of the coupling product obtained with fragment B1 by using NaCNBH 3 (25-50 %).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations